2015
DOI: 10.1038/srep08769
|View full text |Cite
|
Sign up to set email alerts
|

Structure of human dipeptidyl peptidase 10 (DPPY): a modulator of neuronal Kv4 channels

Abstract: The voltage-gated potassium channel family (Kv) constitutes the most diverse class of ion channels in the nervous system. Dipeptidyl peptidase 10 (DPP10) is an inactive peptidase that modulates the electrophysiological properties, cell-surface expression and subcellular localization of voltage-gated potassium channels. As a consequence, DPP10 malfunctioning is associated with neurodegenerative conditions like Alzheimer and fronto-temporal dementia, making this protein an attractive drug target. In this work, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…It has also been reported that the extracellular domain-less DPP6 mutants (DPP6-D-Extra) can bind to and modulate Kv4.2 channels (41). On the other hand, the crystal structure demonstrates that the extracellular domain of DPP6/10 forms a dimeric structure (26,48). DPP4, which is a membrane-bound enzyme and does not modulate Kv4, shows catalytic activity when it forms a dimer (63).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has also been reported that the extracellular domain-less DPP6 mutants (DPP6-D-Extra) can bind to and modulate Kv4.2 channels (41). On the other hand, the crystal structure demonstrates that the extracellular domain of DPP6/10 forms a dimeric structure (26,48). DPP4, which is a membrane-bound enzyme and does not modulate Kv4, shows catalytic activity when it forms a dimer (63).…”
Section: Discussionmentioning
confidence: 99%
“…Because the amino acid identity of the transmembrane domain between DPP6 and DPP10 is high (91%) and the transmembrane domain of DPP10 is important for the binding to Kv4.2, DPP6 may form a heteromultimeric complex with DPP10 (47,48). The combination of Kv4, KChIP, and DPP6/10 in the complex would give rise to further diversity of the biophysical properties and may dynamically regulate cell excitability by a complicated stoichiometry.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations